Interactions between protea plants and their animal mutualists and antagonists are structured more by energetic than morphological trait matching. (1st December 2022) - Neu, Alexander; Cooksley, Huw; Esler, Karen J.; Pauw, Anton; Roets, Francois; Schurr, Frank M.; Schleuning, Matthias
Abstract: Traits mediate mutualistic and antagonistic interactions between plants and animals, and should thus be useful for predicting trophic species interactions. Studies to date have examined the importance of morphological trait matching for plant–animal interactions, but have rarely explored the extent to which these interactions are shaped by matching between energetic provisions of plants and energetic demands of animals. We tested whether energetic and/or morphological trait matching shapes interactions between Protea plant species and their interacting animal mutualists and antagonists in the Cape Floristic Region, South Africa. We recorded interactions between 22 Protea species, pollinating insects and vertebrates as well as seed predators (endophagous insect larvae in protea cones) at 21 study sites. To relate species interactions to matching trait pairs, we measured key morphological traits (shape and size of flower heads and seed cones, and mouth part length as well as body length) and quantified the animals' energetic demands (metabolic rate) together with the plants' energetic provisions (nectar sugar amount, seed‐to‐cone mass ratio). We calculated log ratios of both energetic and morphological traits between animals and plants as predictor variables for the number of observed interactions between Protea species and their animal interaction partners. For both mutualistic and antagonistic interactions, we found significant effects of morphological and energetic trait ratios on the interactions between plants and animals. Trait ratios accounted for 11% to 22% of variation in species interactions. Consistent with energetic trait matching, we found a hump‐shaped relationship between interaction frequency and log ratios of energetic traits of animals and plants, indicating that interactions were most frequent at intermediate log ratios between energetic demand and provision. Effects of morphological trait ratios on interactions were statistically supported in most cases, but were variable in the magnitude and shape of the predicted relationships. Across animal taxa and interaction types, energetic traits had more consistent effects on interactions between plants and animals than morphological traits. This suggests that energy can function as an important interaction currency and facilitate the understanding and prediction of trophic species interactions. Read the free Plain Language Summary for this article on the Journal blog. Abstract : Read the free Plain Language Summary for this article on the Journal blog.